2003
DOI: 10.1186/1472-6823-3-4
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and endocrinologic complications in beta-thalassemia major: a multicenter study in Tehran

Abstract: BackgroundThe combination of transfusion and chelation therapy has dramatically extended the life expectancy of thalassemic patients. The main objective of this study is to determine the prevalence of prominent thalassemia complications.MethodsTwo hundred twenty patients entered the study. Physicians collected demographic and anthropometric data and the history of therapies as well as menstrual histories. Patients have been examined to determine their pubertal status. Serum levels of 25(OH) D, calcium, phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
156
11
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(206 citation statements)
references
References 31 publications
30
156
11
9
Order By: Relevance
“…This figure is quite less than earlier reports. This figure is lower than 57% reported by Satwani et al and 88% reported by Shamshirsaz et al [18,9]. In a multicentre study from Italy involving 1861 patients, hypogonadism was present in 47% of girls older than 15 years of age and secondary amenorrhoea in 23%, menstrual irregularity in 14% and arrest of sexual maturation in 13%.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…This figure is quite less than earlier reports. This figure is lower than 57% reported by Satwani et al and 88% reported by Shamshirsaz et al [18,9]. In a multicentre study from Italy involving 1861 patients, hypogonadism was present in 47% of girls older than 15 years of age and secondary amenorrhoea in 23%, menstrual irregularity in 14% and arrest of sexual maturation in 13%.…”
Section: Discussioncontrasting
confidence: 51%
“…These complications have contributed little to morbidity and mortality in the past; however as a result of increased longevity, these have become more common and contribute significantly to the morbidity in these patients [17]. Endocrine complications along with osteoporosis, trace elements deficiency and other metabolic disturbances also lead to growth failure and short stature [9,10]. Hypogonadism is the most frequent endocrine complication in patients with thalassemia and is an important cause of growth retardation in adolescence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, these cells are most affected, resulting in declining synthesis of luteinizing hormone (LH) and follicle-stimulating hormone (FSH). A study found significant difference in mean serum ferritin level between thalassemic patients with primary amenorrhea, irregular mense, hypogonadism and those without endocrinopathies [10].The current study shows statistically significant low FSH and LH levels as well as significant negative correlation between ferritin and the gonadotrophins in both male and female thalassemic group.…”
Section: Discussionsupporting
confidence: 54%
“…It is still not known whether iron deposition in the pituitary gonadotrophic cells or gondal iron deposition or both causes the hypogonadism. Some studies [10] found significant difference in mean serum ferritin level between thalassemic patients with primary amenorrhea, irregular mense, hypogonadism and those without endocrinopathies. These findings yield the importance of iron overload in development of endocrine disorders among which hypogonadism is most frequent.…”
Section: Introductionmentioning
confidence: 99%